Indonesia's Response to Rohingya Refugees in the Perspective of International Law in 2023 - Siregar, May Proma Rizky (The Easta Journal Law and Human Rights, 2024)
The focus of this research aims to examine how Indonesia's response to Rohingya refugees in the perspective of International Law in 2023. This research uses a qualitative approach with a case study method, after obtaining and researching existing datasets, an evaluation is carried out using qualitative analysis methods. The findings of this research explain Indonesia's response to the Rohingya refugees that occurred in mid-November 2023 with a focus on the perspective of international law. Although Indonesia has not ratified the 1951 Refugee Convention and 1967 Protocol, it has demonstrated engagement that reflects a commitment to the relevant principles of international law. The Indonesian government has given a mandate to UNHCR to handle the protection of Rohingya refugees, Indonesia also seeks international cooperation in dealing with this Rohingya refugee problem, the Indonesian government accepts Rohingya refugees openly because the basis of humanity is stated in Pancasila and the 1945 Constitution as the basis of this country. In addition, Indonesian positive law which contains Article 3 of Presidential Regulation 125/2016 related to the handling of refugees from abroad, and Indonesian national law also contains policies for handling asylum and refugees stipulated in Article 26 of Law 37/1999 as well as the application of the principle of non-refoulement which is applied without exception as the basis for providing assistance and protection to Rohingya refugees.